Nutritional management of the foal with diarrhoea. (30th March 2016) - Barr, B.
Summary: Diarrhoea is a common problem in the neonatal and suckling foal. In certain circumstances supplemental nutrition is necessary depending on the age of foal, severity of diarrhoea and presence of other systemic manifestations. Nutritional supplementation can be provided either enterally or parenterally. Enteral nutrition is superior to parenteral nutrition because it is the most natural and physiologically sound means to provide nutritional support. Parenteral nutrition may be warranted if the foal is unable to receive or tolerate enteral nutrition. Dextrose alone or with amino acids and lipids can provide appropriate nutrition when enteral feeding is not tolerated. As soon as the foal stabilises enteral feeding can be reintroduced.